The Efficacy of CIK-Based Immunotherapies for Advanced Solid Tumors - Chu, Hongjin (Technol Cancer Res Treat, 2016)
OBJECTIVE: To investigate the efficacy of cytokine-induced killer cell-based immunotherapies in patients with advanced malignant solid tumors and the difference in clinical efficiency among 3 kinds of cytokine-induced killer cell-based immunotherapies. METHODS: One hundred forty-six cases with advanced solid tumor, 230 cycles of cytokine-induced killer cell-based immunotherapies, were involved in this study. T-lymphocyte subsets, carcinoembryonic antigen, and adverse reactions were recorded. RESULTS: CD3(+) T lymphocyte, Th, NKT, and Th/Tc were increased after cytokine-induced killer cell-based treatment, from 55.67 ± 3.64 to 84.12 ± 5.15, 26.56 ± 4.47 to 42.76 ± 3.68, 1.82 ± 0.58 to 7.08 ± 0.92, 0.79 ± 3.64 to 1.35 ± 0.20, respectively (P < .001). Carcinoembryonic antigen was decreased from 398.39 ± 219.16 to 127.26 ± 153.41 (P < .001). Difference values were greater than 0 (P < .001). Difference value of carcinoembryonic antigen was obviously less than 0 (P < .001). There was no obvious difference in all variations between cytokine-induced killer cell and DC+CIK groups (P > .05). The highest amount of CD3(+) T lymphocyte and Th was recorded after at least 4 cycles of immunotherapy. And CD8(+) T/CD4(+) T also began to decrease after 4 cycles of immunotherapy. Difference value of T lymphocyte and Tc of patients with surgery is higher than that of patients without surgery. CONCLUSION: Cytokine-induced killer cell-based immunotherapy is capable of increasing T-lymphocyte subsets, recovering cellular immunity without severe side effects, and is suitable for different kinds of solid cancer. Clinical efficiency of cytokine-induced killer cell-based immunotherapy is influenced by many factors such as surgery, stage.